Psychiatric presentation in Rasmussen’s encephalitis - Prashant Maravi; Suneel Singh Kushwaha; Riya Gangwal; Dheerendra Mishra; Nimisha Mishra (Industrial Psychiatry Journal)
Rasmussen’s encephalitis (RE) is a rare neurological disorder characterized by drug-resistant focal epilepsy, progressive hemiplegia, and cognitive decline. While the neurological aspects of RE have been extensively studied, its psychiatric manifestations are often overlooked. This case series presents four illustrative cases of RE with prominent psychiatric symptoms. All cases exhibited a combination of longstanding seizures, developmental delays, and recent-onset psychiatric symptoms, including behavioral disturbances, psychotic features, and altered behavior. Neurological examination revealed characteristic findings such as weakness, tremors, and abnormal reflexes, alongside magnetic resonance imaging evidence of hemicerebral atrophy consistent with RE. Treatment involved a multidisciplinary approach including antiepileptic drugs, antipsychotics, and immunomodulatory therapy. Significant improvements were observed in seizure control and psychiatric symptoms following treatment. Psychiatric manifestations in RE are often attributed to seizure activity and immune responses. RE presents a complex clinical picture with both neurological and psychiatric manifestations. This case series highlights the importance of recognizing and managing psychiatric symptoms in RE to provide comprehensive care to affected individuals.